Developmental outcomes of children with congenital diaphragmatic hernia: a multicenter prospective study - Wynn, Julia (2013)
PURPOSE: To determine developmental outcomes and associated factors in patients with congenital diaphragmatic hernia (CDH) at two years of age. METHODS: This is a multicenter prospective study of a CDH birth cohort. Clinical and socioeconomic data were collected. Bayley Scales of Infant Development (BSID-III) and Vineland Adaptive Behavior Scales (VABS-II) were performed at two years of age. RESULTS: BSID-III and VABS-II assessments were completed on 48 and 49 children, respectively. The BSID-III mean cognitive, language, and motor scores were significantly below the norm mean with average scores of 93 +/− 15, 95 +/−16, and 95 +/− 11. Ten percent (5/47) scored more than two standard deviations below the norm on one or more domains. VABS-II scores were similar to BSID-III scores with mean communication, daily living skills, social, motor, adaptive behavior scores of 97 +/−14, 94+/−16, 93 +/− 13, 97+/− 10, and 94 +/− 14. For the BSID-III, supplemental oxygen at 28 days, a prenatal diagnosis, need for extracorporeal membrane oxygenation (ECMO) and exclusive tube feeds at time of discharge were associated with lower scores. At two years of age, history of hospital readmission and need for tube feeds were associated with lower scores. Lower socioeconomic status correlated with lower developmental scores when adjusted for significant health factors. CONCLUSION: CDH patients on average have lower developmental scores at two years of age compared to the norm. A need for ECMO, oxygen at 28 days of life, ongoing health issues and lower socioeconomic status are factors associated with developmental delays.